Analytical solution of boundary layer flow and heat transfer for non-Newtonian fluids and nanofluid - Wahid, Nur Syahirah (2020)
In this thesis, the boundary layer ow and heat transfer of non-Newtonian fluids and nanouid are studied. The involved non-Newtonian fluids are viscoelastic fluid, Jeffrey fluid and Casson fluid. Meanwhile, for the nanouid, we consider the hybrid nanouid, as it is a recent interesting topic among researchers nowadays. The models are studied over a stretching surface. New additional parameters are being added to the model as to modify, improve, and extend the previous studies. The velocity slip parameter is the main parameter that is being added to all of the fluid models instead of the porosity and thermal radiation parameters. The governing partial differential equations are being reduced to the ordinary differential equations by applying the appropriate similarity transformation. The ordinary differential equations are then being solved by using analytical method with the aid of Maple program. The velocity and temperature profiles are then being plotted. The skin friction and heat transfer coefficients are being tabulated. We found out that the present results show a good agreement as to be compared with the previous studies, which then verify the method we used. From the results obtained, it can be concluded that the effect of the main parameter of the study which is the velocity slip parameter towards both of these fluids are the same for the profiles and the main physical quantities of interest. In which, the increment of the velocity slip parameter has decreased the velocity profile and the local Nusselt number which is the heat transfer coefficient, however, it also has enhanced the temperature profile and the skin friction coefficient for both of the considered fluids that are the non-Newtonian fluids and also hybrid nanouid.